Financial statistical reporting by medical organizations: shortcomings and areas of optimization - M. L. Lazareva; I. V. Tyurina (IRBIS LLC, 2019)
The article discusses some of the shortcomings in financial statistical reports provided by medical organizations in the healthcare sector, namely: duplication and intersection of indicators in different reporting forms, the inconvenient data format for their presentation and analysis, the lack of correlation between indicators of statistical reporting and internal management accounting. To solve these problems, the authors propose the ways of improving the financial reporting by medical organizations: among them, optimizing the system of indicators, abandoning the statistical reporting forms in favor of creating databases (possibly, with outsourcing assistance), as well as creating the uniform rules for maintaining internal management accounting in medical organizations.